Students at Risk of School Failure - José Carlos Núñez (Frontiers Research Topics, 2018)
The main objective of this Research Topic is to determine the conditions that place students at risk of school failure, identifying student and context variables. In spite of the fact that there is currently little doubt about how one learns and how to teach, in some countries of the "developed world," there is still there is a high rate of school failure. Although the term "school failure" is a very complex construct, insofar as its causes, consequences, and development, from the field of educational psychology, the construct "student engagement" has recently gained special interest in an attempt to deal with the serious problem of school failure. School engagement builds on the anatomy of the students' involvement in school and describes their feelings, behaviors, and thoughts about their school experiences. So, engagement is an important component of students' school experience, with a close relationship to achievement and school failure. Children who self-set academic goals, attend school regularly and on time, behave well in class, complete their homework, and study at home are likely to interact adequately with the school social and physical environments and perform well in school. In contrast, children who miss school are more likely to display disruptive behaviors in class, miss homework frequently, exhibit violent behaviors on the playground, fail subjects, be retained and, if the behaviors persist, quit school. Moreover, engagement should also be considered as an important school outcome, eliciting more or less supportive reactions from educators. For example, children who display school-engaged behaviors are likely to receive motivational and instructional support from their teachers. The opposite may also be true. But what makes student engage more or less? The relevant literature indicates that personal variables (e.g., sensory, motor, neurodevelopmental, cognitive, motivational, emotional, behavior problems, learning difficulties, addictions), social and/or cultural variables (e.g., negative family conditions, child abuse, cultural deprivation, ethnic conditions, immigration), or school variables (e.g., coexistence at school, bullying, cyberbullying) may concurrently hinder engagement, preventing the student from acquiring the learnings in the same conditions as the rest of the classmates.